Pain and Complications Assessment in Gynecological Cancer Brachytherapy Patients Under Spinal Anesthesia - Setiawan, Alfredo Abrian Erlangga; Fitrisyah, Aidyl; Zainal, Rizal; Santoso, Budi; Laeto, Arwan Bin (Journal of Anaesthesia and Pain, 2023)
Background: Brachytherapy is a radiation therapy that can deliver radiation to cancer by minimizing radiation exposure to adjacent organs or tissues. In its implementation, brachytherapy can cause pain so that adequate anesthesia is needed in order to get optimal results. This study was aimed to determine the adequacy of anesthesia and complications that occur in gynecological cancer patients undergoing brachytherapy with spinal anesthesia.Methods: A descriptive observational study using primary data that taken by interviewing the patients who underwent gynecological brachytherapy under spinal anesthesia at dr. Mohammad Hoesin Palembang. The number of samples in this study that met the inclusion criteria was 18 subjects. Pain was assessed using an 11-point numeric rating scale. Data were collected in 5 different times, before procedure, during applicator insertion, during radiation process, during applicator removal, and 4 hours after brachytherapy. in addition, all complications that occurred during the procedure were recorded. Data were analyzed to describe the mean, median, minimum, and maximum of pain scores.Result: The average pain score before brachytherapy was 0.78, at the time of applicator insertion was 0, 0.28 at irradiation, 0,11 at removal of the applicator and 1.33 after the brachytherapy procedure. The most common complications were back pain (27.8%) and urinary retention (27.8%).Conclusion: For most patients, high dose rate (HDR) brachytherapy under spinal anesthesia was well tolerated, in fact most patients experienced no pain and no significant life-threatening complications. The post-brachytherapy pain score had the highest average score. Then, back pain and urinary retention were the most common complications.